Responses of Masonry Infill Walls Retrofitted with CFRP, Steel Wire Mesh and Laminated Bars to Blast Loadings - Chen, L.; Fang, Q.; Fan, J.; Zhang, Y.; Hao, Hong; Liu, J. (Multi-Science Publishing, 2014)
Many materials are available for retrofitting masonry infill walls to resist explosion loads. Selection of the most suitable material is essential for optimal performance and cost. In this study, a series of trials were conducted in a specially designed test setup to determine and compare the performances of 1/2-scale masonry infill walls retrofitted with carbon fibre-reinforced polymer strips, steel wire mesh and laminated steel bars, respectively, as well as an unreinforced masonry wall, subjected to blast loads. High fidelity FE models with detail modelling of brick, mortar and retrofitting materials are also developed in LS-DYNA to simulate the blast tests. The accuracy of the FE models in predicting the field blast tests is verified with the test data. The calibrated FE models are used to perform intensive numerical simulations to investigate the effectiveness of various retrofitting measures. The displacement response, failure mode, level of damage and fragmentation from both the field blasting tests and numerical simulations are compared and used to assess the effectiveness of the retrofitting measures. The results demonstrate that the URM retrofitted with steel mesh performed the best among the three retrofitting measures in blast loading resistance, the wall retrofitted with closely spaced CFRP strips performed slightly better than that with steel bars.